2017
DOI: 10.3748/wjg.v23.i34.6350
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of uncut Roux-en-Y vs Billroth II reconstruction after distal gastrectomy for gastric cancer: Which technique is better for avoiding biliary reflux and gastritis?

Abstract: AIMTo identify which technique is better for avoiding biliary reflux and gastritis between uncut Roux-en-Y and Billroth II reconstruction.METHODSA total of 158 patients who underwent laparoscopy-assisted distal gastrectomy for gastric cancer at the First Hospital of Jilin University (Changchun, China) between February 2015 and February 2016 were randomized into two groups: uncut Roux-en-Y (group U) and Billroth II group (group B). Postoperative complications and relevant clinical data were compared between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 17 publications
(17 reference statements)
2
34
1
Order By: Relevance
“…A total of 399 articles considered to be potentially relevant were identified from various databases including PubMed, EMBASE (Ovid), and Cochrane Library (Ovid), 9 studies [ 19 – 27 ] meeting the inclusion criteria were included in this meta-analysis. Literatures screening process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 399 articles considered to be potentially relevant were identified from various databases including PubMed, EMBASE (Ovid), and Cochrane Library (Ovid), 9 studies [ 19 – 27 ] meeting the inclusion criteria were included in this meta-analysis. Literatures screening process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, U-RY reconstruction could prevent reflux gastritis and esophagitis. The U-RY reconstruction could effectively prevent delayed gastric emptying and Roux stasis syndrome by preserving jejunum continuity, integrity of myoelectrical conduction, direction of muscle contraction in the gastrointestinal tract, and normal intestinal peristalsis[ 30 , 31 ]. No significant difference was found in anastomosis-related complications between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies[ 25 - 28 ] reported the occurrence of recanalization at the site of afferent closure after U-RY reconstruction, which may increase the incidence of alkaline reflux gastritis and esophagitis and decrease quality of life. Yang et al[ 31 ] concluded in their study that the incidence of partial recanalization after U-RY reconstruction reached 13.0%. In the included literature, three articles mentioned the problem of recanalization of the obliterated afferent jejunal limb.…”
Section: Discussionmentioning
confidence: 99%
“…URYA can divert biliary and pancreatic secretions away from the remnant stomach more efficiently by blocking the afferent loop and further prevent inflammation and even carcinogenesis of the remnant stomach and esophagus [ 3 5 , 20 , 21 ]. However, the recanalization of the jejunum after surgery may nullify this benefit.…”
Section: Discussionmentioning
confidence: 99%